Prime Archives in Internal Waves - Chen-Yuan Chen (Prime Archives in Internal Waves, 2022)
Internal wave is an important seawater movement, which transmits the energy from the upper layer of the ocean to the deep layer, and then brings the colder seawater in the deep layer together with the nutrients to the warmer shallow layer, which promotes the survival and reproduction of organisms. The internal wave causes the fluctuation of the isodensity surface, which changes the size and direction of the speed of sound, which has a great impact on the sonar, which is conducive to the concealment of submarines under water; it also has a destructive effect on offshore facilities.